B(E2), B(Ml) and 8(E2/ Ml) of Pt (A=198 & (Z=78) Isotope Using IBM-1 - Ibraheim, K.S; TAI-Aiawy, I; Sulaiman, H.T (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Interacting boson model version one has been used in the presenttheoretical calculations. The energy levels & their transitions for dynamical  symmetry  0(6),  SU(3),  U(5),  ground-state  band,  BetaÂ band, Gamma  band, B(E2), Ot, B(Ml), ,u,gt and  6(Â£2/Ml)have been  calculated  to  deduce  the  limit  of  Pt-198,  Z=78.  The  present results  confirmed  the  nuclear  behavior  of  this  isotope  lay  in  thetransitional region 0(6), SU(3) U(5). The calculations of 021 + & 022+showed that the shape of this isotope is oblate according to Q21+  and prolate according to 022+.Most  of  our  results  are  in  good  agreement  with  the  availableexperimental results.